2011
DOI: 10.1016/j.quascirev.2011.06.017
|View full text |Cite
|
Sign up to set email alerts
|

A multi-proxy, high-resolution record of peatland development and its drivers during the last millennium from the subalpine Swiss Alps

Abstract: a b s t r a c tWe present a record of peatland development during the last 1000 years from Mauntschas mire in the eastern Swiss Alps (Upper Engadine valley; 1818 m a.s.l.) inferred from testate amoebae (pH and depth to the water table (DWT) reconstructions), stable oxygen isotopes in Sphagnum (d C correlates with DWT only during AD 1000e1570. Part of this apparent instability among the four time series might be attributed to shifts in the local mire conditions which potentially formed very different (non-analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 52 publications
(62 reference statements)
0
47
1
1
Order By: Relevance
“…Lamentowicz et al (2008a) suggested that the use of δ 13 C values in palaeoecological records reflected the variability in the thickness of the water film on mosses, which is a factor linked to changes in temperature and water table depth. Furthermore, the view of stable carbon isotopes as proxy for mixed signals of temperature and moisture conditions is also supported by an alpine Sphagnum peatland (Mauntschas mire) highresolution record that shows a disagreement between the reconstructed water table and carbon isotope signal (van der Knaap et al, 2011). This disagreement has not been explained sufficiently; however, a species effect caused by changes in the botanical composition of the peat might have produced noise that complicated the interpretation.…”
Section: Trait-based Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Lamentowicz et al (2008a) suggested that the use of δ 13 C values in palaeoecological records reflected the variability in the thickness of the water film on mosses, which is a factor linked to changes in temperature and water table depth. Furthermore, the view of stable carbon isotopes as proxy for mixed signals of temperature and moisture conditions is also supported by an alpine Sphagnum peatland (Mauntschas mire) highresolution record that shows a disagreement between the reconstructed water table and carbon isotope signal (van der Knaap et al, 2011). This disagreement has not been explained sufficiently; however, a species effect caused by changes in the botanical composition of the peat might have produced noise that complicated the interpretation.…”
Section: Trait-based Approachmentioning
confidence: 99%
“…This disagreement has not been explained sufficiently; however, a species effect caused by changes in the botanical composition of the peat might have produced noise that complicated the interpretation. In the Mauntschas mire (van der Knaap et al, 2011), high resolution records that included stable carbon isotope results were compared to the instrumental meteorological time series, and no significant correlations with temperature were revealed (who, whose data, unpublished data).…”
Section: Trait-based Approachmentioning
confidence: 99%
“…However in practice, microsieving makes analysis more efficient particularly when processing large numbers of samples often encountered in palaeoclimate studies and remains routinely employed (e.g. Elliott et al, in press;Lamentowicz et al, 2010;Payne, 2011;van der Knaap et al, 2011). Due to the large number of samples and the need to improve slide clarity for samples with minerogenic material present, the fine sieve stage was included for both contemporary and palaeo sample preparation to retain consistency.…”
Section: Whomentioning
confidence: 99%
“…In the western Swiss Alps and Jura Mountains, for example, palynological studies focussing on the vegetation history during the last several centuries showed that all the mires studied, of supposedly immaculate past history, suffered periods of human-related stress, mostly centred around the 19th century in the form of mire grazing (Van der Sjögren et al 2007). Mauntschas mire in the south-eastern Swiss Alps is yet another effort to find a pristine bog that failed, though the details of its failure differ in exciting ways from the earlier efforts Kamenik et al 2009; Van der Knaap et al 2011). Another new result was the discovery of pollen trends common to the entire western Swiss Alps (see also Van der Knaap et al 2001b;Roos-Barraclough et al 2004;Sjögren et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The longest and most detailed record is that of Mauntschas in the SE Swiss Alps, which covers the entire last millennium at high temporal resolution, approaching annual for the last 150 years. Van der Knaap et al (2011) attempted extracting climate signals from Mauntschas using multiple proxies (pollen-based reconstructions of climate and past vegetation, local surface-moisture and surface-pH reconstructions based on testate amoebae, stable carbon and oxygen isotopes in Sphagnum, local peat accumulation rates, microscopic charcoal, and macro-fossils). The climate signal, however, appeared to be obscured by the anthropogenic signal.…”
Section: Introductionmentioning
confidence: 99%